Some new, rare and interesting desmids from bromeliad phytotelmata in Brazil - Ramos, Geraldo José Peixoto; Bicudo, Carlos Eduardo De Mattos; Moura, Carlos Wallace Do Nascimento (Phytotaxa, 2018)
Studies of the microalgae in bromeliad phytotelmata in northeastern Brazil revealed the occurrence of some interesting desmids—including new and rare taxa, besides new records for South America. Additionally, we reconsidered some taxa previously recorded in the study area, providing new information and ecological data, as well as SEM images. A total of 19 desmids were identified, 18 from Serra da Jiboia (granite outcrops) and one from Itaberaba (in the “Caatinga” dryland domain). Taxonomic notes and ecological characteristics of the studied taxa are included, as well as a checklist of all of the desmids recorded in Brazilian bromeliad phytotelmata.